2015
DOI: 10.1044/2014_jslhr-h-14-0127
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Music Training in Mandarin-Speaking Pediatric Cochlear Implant Users

Abstract: Purpose: The aims of this study were to assess young (5-to 10-year-old) Mandarin-speaking cochlear implant (CI) users' musical pitch perception and to assess the benefits of computer-based home training on performance. Method: Melodic contour identification (MCI) was used to assess musical pitch perception in 14 Mandarin-speaking pediatric CI users; the instrument timbre and the contour length were varied as experimental parameters. Six subjects received subsequent MCI training on their home computer in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 29 publications
(58 reference statements)
8
45
3
5
Order By: Relevance
“…MCI training has been shown to greatly improve MCI performance in postlingual adult English-speaking CI users, with mean post-training performance improving by 28.3 percent points in Galvin et al (2007) and 10.3 percentage points in Galvin et al (2012). More recently, Fu et al (2014) reported large gains in MCI performance in pediatric, prelingually deafened Mandarin-speaking CI users after a moderate amount of home training. In that study, mean baseline performance MCI performance with the piano was 32.8% correct, somewhat higher than the present prelingual performance.…”
Section: Discussionmentioning
confidence: 99%
“…MCI training has been shown to greatly improve MCI performance in postlingual adult English-speaking CI users, with mean post-training performance improving by 28.3 percent points in Galvin et al (2007) and 10.3 percentage points in Galvin et al (2012). More recently, Fu et al (2014) reported large gains in MCI performance in pediatric, prelingually deafened Mandarin-speaking CI users after a moderate amount of home training. In that study, mean baseline performance MCI performance with the piano was 32.8% correct, somewhat higher than the present prelingual performance.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 indicates which studies reported age at testing [17, 18] and implantation [17, 18, 23] or duration of CI use [21]; which variables were integrated into analyses; and whether these factors had significant impact. Some studies [19, 21] enrolled children within a relatively narrow age range, which is likely to result in less maturational variability across participants.…”
Section: Can Training Enhance Music Perception Of Pediatric CI Recmentioning
confidence: 99%
“…In contrast, several training studies provided highly-structured computer-generated training sessions with specific auditory stimuli and highly controlled responses [18, 21], or used a manual outlining specific keyboard exercises [23]. For example, the Fu et al study [18] implemented a computer-generated program presenting melodic contours with differing interval sizes (see Table 3).…”
Section: Can Training Enhance Music Perception Of Pediatric CI Recmentioning
confidence: 99%
See 2 more Smart Citations